Late‐onset eccrine syringofibroadenoma of the feet in a patient with hypohidrotic ectodermal dysplasia. (7th June 2021) - Khan, Hina Ali; Kumarasinghe, Prasad; Wood, Benjamin
Abstract: A 56‐year‐old woman with hypohidrotic ectodermal dysplasia presented with a 10‐year history of persisting wart‐like skin lesions on her feet. Biopsy revealed changes of eccrine syringofibroadenoma. These lesions are rare, with only nine case reports describing an association with ectodermal dysplasia of hidrotic type (Clouston and Schopf's syndrome). To our knowledge, this is the first case of eccrine syringofibroadenoma developing in the hypohidrotic/anhidrotic subtype of ectodermal dysplasia.